Global risk sentiment and the Swiss franc: A time-varying daily factor decomposition model. (April 2022) - Fink, Fabian; Frei, Lukas; Gloede, Oliver
Highlights: Novel multivariate time-varying coefficients model for Swiss franc exchange rates. Decomposing FX returns in three global factors and local uniqueness. Explaining about 73% of the variation in USDCHF and 37% of the variation in EURCHF. Risk contributing the most highlighting safe-haven characteristics of Swiss franc. Episodes of strong momentum present in Swiss franc exchange rate. Abstract: This paper develops an FX factor model to decompose short-term bilateral exchange rate dynamics into different global factors and local uniqueness. We apply the model to the Swiss franc exchange rates against the US dollar (USDCHF) and the euro (EURCHF) between 2006 and 2018 and decompose daily dynamics into three global factors: risk, US dollar, and euro. The model captures daily dynamics well, explaining approximately 73% of the variation in USDCHF and 37% of the variation in EURCHF, reflecting the importance of global factors for Swiss franc exchanges rates. The risk factor contributes the most to Swiss franc dynamics, especially in times of a worsening risk environment, highlighting the role of the Swiss franc as a safe-haven currency. Global factors had been almost completely reflected in USDCHF dynamics before the euro area debt crisis, but once that crisis began, they also became important for EURCHF. In a case study of the introduction of the EURCHF minimum exchange rate we showcase the importance of momentum in daily Swiss franc returns.